(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
With the example of two anthropological accounts from Bosnia-Herzegovina, the author explores the discrepancy between the creators of memory politics and remembrance practices, who are often survivors or political bodies, and the post-war youth audience with its own understanding and—occasionally second-hand—experience of recent violent events. The memory created by one generation is through memory practices passed to the post-war generation, but not necessarily in the way that generation wants to be served. If one is to accept the notion that present memory serves future aspirations, the author argues that it indicates the future generations passively accept their acquired memories, with no critical reflection or fresh response, and an accepted version of social history is constructed out of the memories of their predecessors. This perspective marks every new generation as a mere carrier of past agendas, lacking critical appraisal and autonomous action. This approach condemns every new generation to simply fulfil the future aspirations of their parents. Indeed, this happens and social institutions, like schools and media, support this largely. On the contrary, the author claims that by creating a space for alternative voice of youth, we could hear what the new generations aspire for.